Desastre socioambiental: condições de saúde dos atingidos na perspectiva dos profissionais de saúde e gestores - Camila da Silveira Santos; Alexandra Dias Moreira; Kênia Lara da Silva; Francisco Carlos Félix Lana (Universidade Federal de Santa Maria, 2023)
Objective: to analyze the health conditions of the population affected by the mining dam collapse from the perspective of healthcare professionals and managers. Method: this is a qualitative case study, conducted using public domain documents and interviews with healthcare professionals and managers, from March to May 2022, totaling 14 participants. The data were analyzed according to the theoretical propositions strategy based on the Social Determinants of Health. Results: the health conditions of this population have worsened in terms of respiratory problems, gastroenteritis, obesity, arboviruses, increased use of alcohol and drugs, and mental illnesses. The loss of employment, home, and community belonging of those affected is highlighted. Conclusion: the socio-environmental disaster was a conditioning factor for changes in the health conditions of those affected, exposing them to new scenarios and overlapping risks capable of modifying their quality of life and aggravating their biopsychosocial health conditions.